Automatic generation of reaction energy databases from highly accurate atomization energy benchmark sets. Issue 15 (31st March 2017) - Margraf, Johannes T.; Ranasinghe, Duminda S.; Bartlett, Rodney J.
Abstract : We describe the automatic generation of reaction energy benchmark sets from arbitrary atomization energy reference data. Abstract : In this contribution, we discuss how reaction energy benchmark sets can automatically be created from arbitrary atomization energy databases. As an example, over 11 000 reaction energies derived from the W4-11 database, as well as some relevant subsets are reported. Importantly, there is only very modest computational overhead involved in computing >11 000 reaction energies compared to 140 atomization energies, since the rate-determining step for either benchmark is performing the same 140 quantum chemical calculations. The performance of commonly used electronic structure methods for the new database is analyzed. This allows investigating the relationship between the performances for atomization and reaction energy benchmarks based on an identical set of molecules. The atomization energy is found to be a weak predictor for the overall usefulness of a method. The performance of density functional approximations in light of the number of empirically optimized parameters used in their design is also discussed.